Enhancement in the stability of alginate gels prepared with mixed solution of divalent ions using a diffusion through dialysis tube (DTDT) approach. Issue 5 (4th May 2017) - Bajpai, M.; Shukla, Priyanka; Bajpai, S. K.
ABSTRACT: In this work, calcium alginate hydrogels have been prepared by a new technique, called 'diffusion through dialysis tube' (DTDT) which involved transfer of crosslinking ions into alginate solution via a dialysis tube with a molecular weight cutoff of 8 k Da. The various hydrogels, prepared with varying degree of crosslinking, were characterized by FTIR, XRD and TG analysis. We also investigated their dynamic water absorbency in phosphate buffer saline (PBS) of pH 7.4 and the data were interpreted in terms of various kinetic models. The equilibrium water uptake data was used to determine network parameters of hydrogels. Finally, the stability and water absorbency of these hydrogels were enhanced to a desired level by using crosslinker solutions, composed of Ba ++ /Ca ++ and Zn ++ / Ca ++ ions.